Comparison of the digestibility of three forage species estimated by different techniques (Orinoquia, 2018)
This research was conducted in the Villavicencio city, at the Universidad de los Llanos, whose objective was to determine the digestibility of three forages for cattle through four different techniques: one in situ and three in vitro (inoculation with ruminal fluid, gas production, and enzymatic), in order to validate the techniques and equipment that are being used for these procedures; the forage species were evaluated: Pennisetum purpureum, Hibiscus rosa-sinensis y Gliricidia sepium, in addition it was evaluated both in all techniques: the curve and rate of degradation of dry matter (DM), neutral detergent fiber (NDF) and crude protein (PC) (0 to 72 hours). A repeated measures design was used, under which the analysis of variance was performed to determine the ranges of deviation between the techniques and thus establish the trend of the data; the variables evaluated were the digestibilities of DM, NDF and PC of the three forages of the four techniques; after verifying the differences between the variances of the digestibilities, and check the assumption of sphericity with the Mauchly test, the multiple comparison was performed with the Bonferroni test. The digestibility of DM, NDF and PC varied between 39.89-44.22, 54.18-64.26 and 47.54-57.05%; 79.29-84.18, 76.30-86.95 and 72.81-89.03%; 32.52-62.14, 69.12-76.52 and 42.00-66.54% respectively in the PP, HR and GS forages, depending on the technique used for their estimation. Despite finding statistically significant differences among several of the comparisons made in the techniques of digestibility, it was found a high determination coefficient and correlation between estimates in vitro: inoculation with ruminal fluid, gas production and enzymatic with respect to the in situ estimate.
Keywords: Shrubs; digestion; cultivated forages; nutrients; nutritional supplementation